Analisis Estetika Karya Galih Reza Suseno Yang Berjudul ‘Lunar In Nibiru’ - Nafisa Aqilah; Miftahul Falah; Mertien Roos (VisArt: Jurnal Seni Rupa dan Design, 2025)
This study discusses aesthetics and creative process in creating a painting, with a case study on the work "Lunar in Nibiru" by Galih Reza Suseno. The artist's creative process is expressed through the Alma Hawkins theoretical approach which includes three main stages: exploration, improvisation, and formation. The inspiration for the main work comes from personal experiences, especially the surreal dreams experienced by the artist during the Covid-19 pandemic. The study uses a qualitative descriptive method with data collection through literature studies and observations of the Srissanti Syndicate archives. The results of the study show that Galih Reza Suseno's creative process involves searching for ideas from subconscious experiences, exploring embossed painting techniques with acrylic media on canvas, and improvising in selecting visual elements to achieve the desired aesthetic quality. This study emphasizes the importance of personal meaning and exploration techniques in producing original and communicative works of art. The achievements of this research are expected to be able to provide contributions and also references for other painters and academics who use Galih Reza Suseno's works as a source of inspiration and also an object of study.